Cidade (Re)vista : interpretação decolonial da fotografia de Naiara Jinknss em Belém do Pará - SANTA BRÍGIDA, Juliane Oliveira (Universidade Federal do Pará, 2023)
This research focused on the imagetic production of the documentary photographer Naiara Jinknss, focusing on the content posted on her Instagram during 2019, in order to understand from a decolonial interpretation the role of her photography as an image of resistance. Therefore, the overall aim seeks to answer the following question: "how can Naiara Jinknss's photographic production be interpreted as an image of resistance within the power relations present in the discourse on the Amazon?". Through netnographic inspirations in Kozinets (2014) and phenomenological-decolonial approach, anchored in the phenomenological sociology of Schutz (1979), the understanding that phenomena and experiences are conditioned to the social and, therefore, transmitted in society was adopted. While exploring research objects that are immersed in the context of a country built by coloniality, it is a fact that the phenomena and experiences analyzed are also involved in what Quijano (1992) calls the colonial matrix of power. Therefore, we seek to develop the articulation of the concepts of Kossoy (2001), Aumont (2002), Fairclough (2001), Bhabha (1998), Hall (2006), Quijano (1992), Mignolo (2015), Maldonado-Torres (2017), among others. The research methodology developed included a bibliographic survey on the Amazon, Power and Photography, in the area of Social Sciences, and multiple stages of online data collection. The relevance of this study is trusted in highlighting the photographic production made by a professional from Pará who identifies with several minority groups in front of a field traditionally marked by power relations that do not contemplate these groups and that is not exempt from discourses and imaginary reproduced on the Amazon.